2010
DOI: 10.1021/jo101337a
|View full text |Cite
|
Sign up to set email alerts
|

Charged Tags as Probes for Analyzing Organometallic Intermediates and Monitoring Cross-Coupling Reactions by Electrospray-Ionization Mass Spectrometry

Abstract: Organic iodides bearing a cationic quaternary ammonium group at a remote position react with zerovalent Pd complexes, Zn, or In leading to a C-I bond insertion. The resulting charge-tagged organometallics can be detected by electrospray-ionization mass spectrometry, which provides detailed information on their stoichiometry, oxidation state, and coordination sphere. The properties of the observed organopalladium and -zinc intermediates largely agree with previous findings, whereas the organoindium species show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
49
0
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(56 citation statements)
references
References 84 publications
(54 reference statements)
3
49
0
4
Order By: Relevance
“…While ESI-MS analysis of this type can reveal the presence of any low-concentration potential intermediates, simple detection of a low concentration species does not clarify its role in the overall solution phase reaction. In order to understand the role of observed species it would be highly desirable to monitor the reaction profile of key species continuously over the course of the reaction in such a way that kinetic data can be obtained [8,18,89,92]. A few groups, including our own, have worked to develop such methodology.…”
Section: Continuous Reaction Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…While ESI-MS analysis of this type can reveal the presence of any low-concentration potential intermediates, simple detection of a low concentration species does not clarify its role in the overall solution phase reaction. In order to understand the role of observed species it would be highly desirable to monitor the reaction profile of key species continuously over the course of the reaction in such a way that kinetic data can be obtained [8,18,89,92]. A few groups, including our own, have worked to develop such methodology.…”
Section: Continuous Reaction Monitoringmentioning
confidence: 99%
“…Nevertheless, this work demonstrates the potential of reaction-monitoring by ESI-MS to provide substantial mechanistic insights. In 2010, a palladium-catalyzed Negishi cross-coupling reaction between the quaternary ammonium charged substrate (p-iodophenyl)-trimethyl-ammonium iodide ([ArI] + I -) and benzylzincbromide to form (p-benzylphenyl)-trimethyl-ammonium iodide ([ArBn] + I -) was monitored continuously using ESI-MS [89]. Reaction mixtures were drawn into a syringe and injected continuously at room temperature into the mass spectrometer over 30 minutes beginning approximately 2 minutes after the start of the reaction ( Figure 22).…”
Section: Continuous Reaction Monitoringmentioning
confidence: 99%
“…Reductive elimination from well-defined Pd(IV) complexes, shown for C-C bond formation by Canty et al [17] and for C-O bond formation by Sanford et al [3,18,19] has been observed. Just recently we studied the reaction mechanism of palladium-catalyzed intramolecular oxidative aryltrifluoromethylation reaction and characterized several important Pd(IV) transient intermediates involved in the reaction solution by ESI-MS. [12] Base on the previous studies on this kind of reaction mechanism and reported works about studying the Pd species in reaction systems by ESI-MS/MS technique, [20][21][22] in this study, we selected the classic Pd(OAc) 2 -catalyzed oxidative coupling reactions (Scheme 1) and tried to study the reactive Pd(IV) transient intermediates in the reaction solution and test their intrinsic reactivity of the transient intermediates fully by using ESI-MS/MS technique. ESI is a soft ionization tool used extensively in identifying organometallic reaction transient intermediates to study reaction mechanism with transferring the reactive transient intermediates from solution to the gas phase.…”
Section: Introductionmentioning
confidence: 99%
“…To again overcome this limitation, the elegant concept of charged tags developed in the gas phase [9] was brought into solution to facilitate the "flight to the moon", as Scheme 1 exemplifies. [10] In his Nobel lecture, [11] Fenn summarized ESI as "wings for molecular elephants"; similarly, the combination of ESI and charged tags can be viewed as "charged wings for the flying fish of reaction intermediates" (Figure 1). …”
mentioning
confidence: 99%